The accuracy of non-invasive blood pressure monitoring when compared to intra-arterial blood pressure monitoring in patients with severe pre-eclampsia during an acute hypertensive crisis - Dalla, Sangita (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Obstetrics and Gynaecology))--University of Stellenbosch, 2010.